Program Pengembangan Kemampuan Kognitif Anak Usia Dini Melalui Kegiatan Meronce Menggunakan Bahan Alam - Kasiyati, Kasiyati (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2023)
The purpose of this study is to ascertain whether children's cognitive capacities may be enhanced by natural material merging activities. There were twenty-five kids in Group B2 Kartika PGRI Tambakmulyo Kindergarten who served as the research subjects. Cycle I showed the start of the research implementation, which concluded in Cycle II. Every cycle involves the following four steps: planning, implementation, observation, and reflection. Documentation and observation sheets were employed as data gathering strategies. This study employs a quantitative, descriptive data analysis methodology. Preliminary assessments prior to the intervention revealed that 20% of the participants had complete cognitive competence. Cycle I showed an increase in the use of natural material-assisted merging operations to 56% of the participants, and Cycle II has reached the success indicator of 88%. These findings suggest that the raffling exercise, when aided by natural materials, can enhance the cognitive capacities of the kids in Group B. Kindergarten Kartika PGRI Tambakmulyo.